ACCRETION ONTO A MAGNETIC DIPOLE: RESULTS OF 2D NUMERICAL SIMULATIONS - Toropin, Yu. M.; Toropina, O. D. (Одеські астрономічні публікації, 2017)
Different regimes of accretion to a star with a dipole magnetic field were investigated using 2D numerical axisymmetric resistive MHD simulations. Numerical technique was improved over our recently published results (Toropin et al., 1999, referred as T99 below). A new model for the gravitating star with a dipole magnetic field was adopted for presented simulation set. Spherical accretion to a non-rotating star with a dipole field was modeled. Existence of the stationary accretion flow with polar columns inside the Alfven surface was confirmed. The accretion rate to the dipole in the axially symmetric flow is always smaller than in the Bondi accretion to corresponding non-magnetized star. Investigations of the cylindrical accretion (parallel to the star's magnetic momentum) were started. If the value of the star's gravitational capture radius is close to its Alfven radius then the magnetic field surveys as an effective obstacle for the incoming flow deflecting it from the star. Simulated flow structure is discussed.